Biological and physicochemical studies of oleyl oleate as an active agent to be applied in cosmetic formulation - Shaiful Bahri, Fadhlin Hasya; Mat Radzi, Salina; Mohd Amin, Nur Amalina; Mohd Rehan, Maryam; Abdul Rahman, Nurul Jannah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study aimed to synthesize oleyl oleate via esterification, confirm its structure using spectroscopic methods, and evaluate its antimicrobial properties and physicochemical characteristics for cosmetic use. Oleyl oleate synthesis was confirmed with FTIR and NMR spectroscopy. Oleic acid and oleyl alcohol were reacted in a 1:2 molar ratio at 50°C for 5 hours in hexane. The product yield was approximately 85%. Antimicrobial activity was tested against Gram-positive and Gram-negative bacteria using agar diffusion method, Minimum Inhibition Concentration (MIC), and Minimum Bactericidal Concentration (MBC) assays against Gram-positive and Gram-negative bacteria. Dilutions of 1:1 to 1:4 (v/v) were tested, and the bacterial inoculum was standardized to 107 cells/mL. The compound showed higher activity against Gram-positive bacteria, with MBC of 1:2 (v/v) for Bacillus subtilis. Physicochemical properties such as Sun Protection Factor (SPF), peroxide value, saponification value, and iodine value were also measured. Physicochemical assessments yielded an SPF value of 8.0, peroxide value of 17.98 meq/kg, saponification value of 82.48 mg KOH/g, and iodine value of 82.37 g/100g. These properties meet cosmetic ingredient standards. Unlike traditional extraction methods that rely on limited and costly natural wax sources like jojoba oil, this study demonstrates a simple, catalyst-free synthetic route using readily available materials, offering a scalable and economical alternative. The study demonstrates that oleyl oleate has notable antimicrobial activity, particularly against Gram-positive bacteria, and physicochemical properties suitable for cosmetic formulations, indicating its potential for widespread use in the cosmetic industry.